Presença do gene BRU1 e comportamento diferencial de genótipos de cana-de-açúcar e acessos exóticos a Puccinia melanocephala - Neuber, Ana Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is known that the use of molecular markers is an important tool which allows the identification of superior individuals in juvenile stages speeding up the cultivar development process. Sugarcane brown rust caused by the fungus Puccinia melanocephala is among the most important sugarcane diseases. Recently, two diagnostic molecular markers (R12H16, 9O20-F4) flanking the Bru1 gene, which is pointed as the major gene conferring brown rust resistance reported for sugarcane today were publish in the literature. The present study aimed to determine the frequency of the Bru1 gene in sugarcane exotic accessions, Brazilian varieties and elite clones from IAC program as well as to evaluate the efficiency of these markers to identify resistant genotypes. By using the Bru1 markers, it was possible to infer the frequency of Bru1 gene, and compare the results with the phenotypic classification of sugarcane Brazilian varieties and IAC clones (IAC, CTC, SP and RB) for susceptibility to the disease. Moreover, S. spontaneum, S. sinense and S. robustum accessions were artificially inoculated with the fungus P. melanocephala and weekly evaluated in greenhouse conditions. The degree of brown rust susceptibility of the accessions was compared with the presence or absence of Bru1 gene markers. The frequency of the Bru1 gene in the Brazilian varieties was high (75.21%) while only 18% of the sugarcane exotic accessions showed the Bru1 gene. Most of the varieties that presented the gene were classified as resistant. Low marker-phenotypic correlation was observed for the artificially inoculated sugarcane exotic accessions, probably due to the presence of other sources of resistance or failure of the sequence complementarity of the primers in the genome of these accesses. Generally these markers proved to be efficient in the selection of genotypes resistant to brown-rust

É sabido que a utilização de marcadores moleculares em programas de melhoramento constitui uma ferramenta importante, pois permite identificar indivíduos superiores em fases juvenis, acelerando o processo de desenvolvimento de cultivares. A ferrugem marrom é uma doença causada pelo fungo Puccinia melancephala responsável por grandes prejuízos no setor canavieiro. Recentemente foram desenvolvidos marcadores moleculares, 9020-F4 e R12H16, os quais flanqueiam o maior gene de resistência à ferrugem marrom, conhecido como Bru1. O presente trabalho objetivou determinar a frequência do gene Bru1 em acessos exóticos de cana-de-açúcar, cultivares brasileiras e clones do Programa IAC bem como avaliar a sua eficiência na identificação de genótipos resistentes. Através da reação de PCR utilizando os marcadores, foi possível inferir a frequência do gene Bru1, e comparar esses resultados com a classificação fenotípica das cultivares brasileiras e clones IAC (IAC, CTC, SP e RB), quanto à suscetibilidade a doença. Além disso, foi conduzido um experimento em casa de vegetação, utilizando acessos de Saccharum spontaneum, Saccharum sinense e Saccharum robustum, os quais foram inoculados artificialmente com o fungo Puccinia melanocephala e avaliados semanalmente visando determinar o grau de suscetibilidade à ferrugem marrom. Posteriormente, os resultados obtidos foram comparados com a presença ou ausência do gene Bru1. Nas cultivares brasileiras a frequência do gene Bru1 foi alta, 75,21%, porém nos acessos exóticos foi de apenas 18 %. Verificou-se que grande parte das cultivares que possuem o gene Bru1 é classificada como resistente. Nos acessos exóticos inoculados artificialmente, a correlação entre a presença dos marcadores indicativos do gene Bru1 com as notas de severidade foi baixa e não significativa, provavelmente devido à presença de outra fonte de resistência...
Survey of the BRU1 Gene and differential behavior of sugarcane genotypes and wild acess to Puccinia melanocephala
Keywords: Cana-de-açúcar; Genes; Genetica vegetal; Puccinia; Marcadores genéticos; Pragas agricolas; Genetic markers; Agricultural pests